China's commercial building carbon emissions toward 2060: An integrated dynamic emission assessment model. (1st November 2022) - Huo, Tengfei; Xu, Linbo; Liu, Bingsheng; Cai, Weiguang; Feng, Wei
Graphical abstract: Highlights: Establishes an integrated dynamic emission assessment model by coupling end-use energy model and system dynamics model. Explores the dynamic interaction mechanism between macrolevel and microlevel factors as well as technical options. Commercial buildings will probably hit the emission peak at 1.28Gt CO2 in 2037 under the BAU scenario. Lighting and cooling will contribute over 70% to the carbon emission growth. Technological progress, clean energy, and electrification rate play significant roles in boosting emission peak and peaking time. Abstract: Carbon-mitigation in the commercial building sector is critical to carbon peaking and carbon neutral commitment. However, there has been little scientific focus on long-term evolutionary trajectories and peak path in this sector. This study innovatively develops an integrated dynamic emission assessment model (IDEAM) by combining the system dynamics model with the bottom-up end-use energy model. Moreover, the IDEAM is combined with the scenario analysis approach to model the dynamic evolution of Chinese commercial building carbon emissions toward 2060. The results show that commercial building carbon emissions will peak at 1.28 Gigatons (Gt) of CO2 in 2037 under the baseline scenario and will advance toward 2029 with an emissions peak of 0.98 Gt CO2 under the low-carbon scenario. Cooling and lighting are the two end-uses that contribute most to the growth of carbon emissions at over 70%. These two end-uses indicate different carbon-abatement potentials across climate zones. Sensitivity analysis reveals that promoting technological progress, increasing the share of clean energy, and improving low-carbon awareness are major ways to facilitate the early realization of carbon peaks and carbon neutrality. This study provides a deeper understanding of possible emission pathways and could assist policy-makers in devising scientific carbon mitigation plans.